Selective bronchial artery embolization in hemoptysis: A retrospective study - Idil Soylu, Aysegul; Uzunkaya, Fatih (Annals of Medical Research, 2021)
Aim: The aim of this study was to evaluate the efficacy and outcome of BAE in hemoptysis patients. Selective bronchial artery embolization (BAE) is a minimally invasive treatment method developed alternative to surgery for acute recurrent hemoptysis.Material and Methods: The data of patients who underwent BAE with hemoptysis was collected retrospectively. The etiology of hemoptysis, localization and type of lesion, embolizing agent used and postoperative complications were recorded. Lesions were classified as pathological hypervascularity, arteriovenous fistula (AVF) and extravasation.Results: A total of 17 patients were included in this study. The most common underlying cause for hemoptysis was tuberculosis (% 40). Embolizing agents used were microspheres in 13 patients, n-BCA iodized oil mixture in 2 patients, polyvinyl alcohol particles in 1 patient and vascular plug in 1 patient. In the first 30 days after the procedures, bleeding completely stopped in 94,2% of the cases. Four patients (1 on 3rd day, 3 in 15-19 months) required re-embolization. Bronchial artery embolization was performed only once in 13 patients (76.4%), twice-in three patients (17.6%) and 3 times in 1 patient (5.8%).Conclusion: We concluded that BAE is a safe, effective and minimally invasive method that can be performed repeatedly for treatment of hemoptysis.
Keywords: Hemoptysis; bronchial artery embolization; endovascular treatment.